2003
DOI: 10.1002/mus.10472
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study of fk506 in patients with myasthenia gravis

Abstract: To investigate the usefulness of low-dose FK506 for the treatment of myasthenia gravis (MG), we treated 19 patients with generalized MG in a 16-week open clinical trial of FK506 (3-5 mg/day). At the end of the trial, total MG scores (range: 0-27 points) improved by 3 points or more in 7 of 19 patients (37%), and activities of daily living (ADL) scores (range: 0-6 points) also improved by 1 point or more in 8 of 19 patients (42%). Nine of 19 patients (47%) showed improvement in either MG or ADL scores. Signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 77 publications
3
76
0
Order By: Relevance
“…Various clinical situations have been studied, such as in patients refractory to, or intolerant of, corticosteroids or additional immunosuppression, presence of thymoma, and in patients with a relatively new diagnosis. The most common dosing strategies were: a fixed daily dose of 3 mg with or without assessment of trough drug concentrations; and a weight-based approach of 0.1 mg/kg/day in divided doses with dosage titrated to achieve a trough concentration of 7-8 ng/ml [Shimojima et al 2006;Nagaishi et al 2008;Tada et al 2006;Konishi et al 2003Konishi et al , 2005Zhao et al 2011;Yoshikawa et al 2011;Ponseti et al 2005aPonseti et al , 2005bPonseti et al , 2006Nagane et al 2005;Mitsui et al 2007]. While the weight-based regimen is within the manufacturer's dosing recommendations for prevention of transplant rejection, the 3 mg dose falls below the FDA-approved dosing range [Astellas Pharma, 2013].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various clinical situations have been studied, such as in patients refractory to, or intolerant of, corticosteroids or additional immunosuppression, presence of thymoma, and in patients with a relatively new diagnosis. The most common dosing strategies were: a fixed daily dose of 3 mg with or without assessment of trough drug concentrations; and a weight-based approach of 0.1 mg/kg/day in divided doses with dosage titrated to achieve a trough concentration of 7-8 ng/ml [Shimojima et al 2006;Nagaishi et al 2008;Tada et al 2006;Konishi et al 2003Konishi et al , 2005Zhao et al 2011;Yoshikawa et al 2011;Ponseti et al 2005aPonseti et al , 2005bPonseti et al , 2006Nagane et al 2005;Mitsui et al 2007]. While the weight-based regimen is within the manufacturer's dosing recommendations for prevention of transplant rejection, the 3 mg dose falls below the FDA-approved dosing range [Astellas Pharma, 2013].…”
Section: Discussionmentioning
confidence: 99%
“…Citations of retrieved articles were also examined for relevance and included if applicable. A total of 12 studies met inclusion criteria [Shimojima et al 2006;Nagaishi et al 2008;Tada et al 2006;Konishi et al 2003Konishi et al , 2005Zhao et al 2011;Yoshikawa et al 2011;Ponseti et al 2005aPonseti et al , 2005bPonseti et al , 2006Nagane et al 2005;Mitsui et al 2007]. Table 2 provides a summary of the pertinent findings from each trial.…”
Section: Data Sourcesmentioning
confidence: 99%
“…Therefore, the development of new means to treat MG and to prevent recurrence is necessary. Although tacrolimus hydrate (FK506) has recently been approved for this purpose, 24) it causes severe adverse effects, such as renal toxicity and opportunistic infection.…”
Section: Discussionmentioning
confidence: 99%
“…FK506 has been proven safe and effective in preventing organ rejection in clinical organ transplantation [8]. Furthermore, in noncontrolled studies, it has been observed that even a low dose of FK506 can be used as an effective supplementary treatment for MG and produces no significant side effects [9,10,11]. In the present study, we examined the efficacy of low-dose FK506 for treatment of de novo MG patients in a randomized prospective clinical trial.…”
Section: Introductionmentioning
confidence: 99%